The Silurian inception of inland desert ecosystems: trace fossil evidence from the Mereenie Sandstone, Northern Territory, Australia - Shillito, AP; Davies, NS (Geological Society of London, 2021)
The Silurian was an interval of profound change in terrestrial ecosystems as the earliest non-marine animal communities began to become established on the continents. Whilst much is known about the transition of pioneering animals from shallow marine to coastal and alluvial habitats, evidence for animal activity in contemporaneous aeolian strata is rare. Here, we present trace fossil evidence that closes this knowledge gap, indicating that Silurian desert environments, dominated by aeolian processes, were occupied by resident invertebrate communities. The evidence comes from the Mereenie Sandstone, Northern Territory, Australia, which is demonstrated to have been deposited in a wet inland aeolian system, typified by small crescentic sand dunes and extensive interdune flats. The invertebrate trace fossil associations from the Mereenie Sandstone (Arenicolites isp., “Burrow entrance with radial feeding traces”, Didymaulichnus lyelli, Diplichnites gouldi, Helminthopsis isp., Laevicyclus isp., Palaeophycus isp., Polarichnus garnierensis, Skolithos isp.) are restricted to damp interdune deposits, whereas dune strata are barren. The ichnofauna are described and compared to those from other Palaeozoic aeolian systems, in order to re-evaluate the timing of the early stages of arthropod terrestrialization.